EFEKTIVITAS LAYANAN INFORMASI UNTUK MENINGKATKAN KOMUNIKASI ANTAR PRIBADI PADA SISWA KELAS X MAN 1 ACEH TENGGARA - Putri Raihanun Al Fatha (Al-Mursyid : Jurnal Ikatan Alumni Bimbingan dan Konseling Islam (IKABKI), 2019)
Communication is one thing that is very important in the process of life. Most of the time that humans have is used for communication. The quality and ability to communicate isa measure of the extent to which a person can be accepted or not social environment. Through communication, individuals can understand each other and know information about their surroundings so that they are able to take actions and decisions in response to the information provided. Interpersonal communication is a form of communication that is effective in changing attitudes, opinions and communicant behavior.  Interpersonal communication can be interpreted as a message sent by someone to another person either one person or more with a view to influencing the other person's behavior. Therefore,information services are needed to help students better understand the consequences of interpersonal communication itself that it is important to have good interpersonalcommunication skills. Based on this, the purpose of this study was to determine an increase in interpersonal communication between students after being provided with information services at MAN 1Aceh Tenggara. After doing research, it was found that information services proved effective in improving the quality of interpersonal communication among students at MAN 1 AcehTenggara. Effectiveness occurs with an increase in the quality of interpersonal communication between students through scores obtained in the pre-test, cycle I and the results of the second cycle test which has increased, where the average results of the qualityof interpersonal communication of students in the pre-test 45,15, results the first cycle test is 53.24, and the results of the second cycle test is 86.76.Keywords: Information Services, Interpersonal Communication